Muscle-specific neuromuscular responses during running with blood flow restriction - Lubiak, Sean M.; Proppe, Christopher E.; Rivera, Paola M.; Howard, Mason A.; Prajapati, Anuj J.; Shah, Niriham M.; Patel, Nihar N.; Hammer, Shane M.; Trevino, Michael A.; Dinyer-McNeely, Taylor K.; Zak, Roksana B.; Hill, Ethan C. (International Journal of Sports Medicine, 2025)
The purpose of this investigation was to examine muscle excitation at maximal running capacity without blood flow restriction (BFR) relative to submaximal running bouts with BFR. Fourteen college-aged males randomly completed four, three-minute running bouts at 70, 80, and 90% of peak speed with BFR (70%BFR, 80%BFR, and 90%BFR) and without BFR at 100% of their peak speed (100%NOBFR). The surface electromyographic amplitudes of the vastus lateralis, rectus femoris, and vastus medialis muscles were assessed. Muscle excitation of the vastus lateralis was similar across most bouts; however, it was lower during the 70%BFR compared to 90%BFR (Meandiff =−4.67±− 0.22%; Bayesian 95% high-density interval [HDI]: − 7.07 to − 2.2) and 100%NOBFR (Meandiff =−2.94±− 0.27%; 95% HDI:−5.33 to−0.50) bouts. For the rectus femoris, muscle excitation largely increased across running speeds (70%BFR<80%BFR < 90%BFR; 90%BFR < 100%NOBFR). For the vastus medialis, muscle excitation was lower during the 70%BFR compared to 90%BFR (Meandiff =−8.15±− 0.28%; 95% HDI:−15.3 to−0.89). Submaximal running with BFR increased muscle excitation responses for the vastus lateralis and vastus medialis, such that muscle excitation was similar to 100%BFR, despite 10–20% reductions in running speed. The rectus femoris muscle, however, was not affected by BFR during the submaximal running bouts.
Keywords: blood flow restriction; electromyography; electromyography